Parametric analysis of ethylene oxide synthesis in a catalytic microchannel reactor - Eyvaz, Hatice. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
In this study, ethylene oxide synthesis over Ag/α-Al2O3 is investigated in a catalytic microchannel reactor by COMSOL software. Microreactors are ideal devices to investigate highly exothermic reactions like ethylene oxide synthesis. These units can be run without risk of explosion with explosive reagents and with minimized transport resistances. Therefore, microchannel reactor geometry is used for simulation studies with the aim of investigating the effect of different feed temperatures and feedstock compositions on ethylene oxide synthesis. The two dimensional (2D) catalyst coated channel geometry is simulated by COMSOL MultiphysicsTM using finite element method under isothermal conditions. Before the 2D simulation tests, the kinetic model obtained from the literature is validated by the experimental data adapted from the already published studies. When the higher feed temperatures are used in the simulations, ethylene conversion increases and the selectivity of ethylene oxide decreases. The maximum conversion value of 13.8% is obtained at 565 K and for Set 1 in 2D simulations. This conversion value is smaller than 1D simulation result (61%) which is obtained for the same operation conditions. The feed ratio, C2H4/O2 should be small for higher selectivity and conversion values. Small C2H4/O2 ratios and lower temperature values (483 K, 513 K) enhances the selectivity of EO. With the increase in temperature total oxidation of ethylene become dominant and the selectivity of ethylene oxide decreases.
Keywords: Catalytic reforming.; Oxides.; Microchemistry.; Chemical reactors.